Microbubble Distillation for Ethanol-Water Separation - Atheer Al-yaqoobi; David Hogg; William B. Zimmerman (International Journal of Chemical Engineering)
In the current study, a novel approach for separating ethanol-water mixture by microbubble distillation technology was investigated. Traditional distillation processes require large amounts of energy to raise the liquid to its boiling point to effect removal of volatile components. The concept of microbubble distillation by comparison is to heat the gas phase rather than the liquid phase to achieve separation. The removal of ethanol from the thermally sensitive fermentation broths was taken as a case of study. Consequently the results were then compared with those which could be obtained under equilibrium conditions expected in an “ideal” distillation unit. Microbubble distillation has achieved vapour compositions higher than that which could be obtained under traditional equilibrium conditions. The separation was achieved at liquid temperature significantly less than the boiling point of the mixture. In addition, it was observed that the separation efficiency of the microbubble distillation could be increased by raising the injected air temperature, while the temperature of the liquid mixture increased only moderately. The separation efficiency of microbubble distillation was compared with that of pervaporation for the recovery of bioethanol from the thermally sensitive fermentation broths. The technology could be controlled to give high separation and energy efficiency. This could contribute to improving commercial viability of biofuel production and other coproducts of biorefinery processing.